Evaluation of the iHEART mental health education programme on resilience and well-being of UK secondary school adolescents. Issue 1 (13th January 2021) - Kelley, Thomas; Kessel, Anthony; Collings, Rosalyn; Rubenstein, Brian; Monnickendam, Charlotte; Solomon, Andrew
Abstract : Purpose: The purpose of this paper is to present the findings of a preliminary study based on a novel structured mental health education programme – Innate Health Education and Resilience Training (iHEART) – in a cohort of secondary school adolescents in the UK. Design/methodology/approach: A curriculum-based ten-week programme was delivered by trained facilitators. In total, 205 students enrolled in the study. An additional 64 participants were within an age-matched non-intervention control group. A non-randomised control mixed methodology approach was used. All students, pre- and post-programme, completed a quantitative questionnaire – the Warwick-Edinburgh Mental Well-being Survey. Qualitative measures were used to assess participants' perceptions of changes in their resilience and mental well-being. Findings: Those who received the intervention showed a small improvement in mental well-being relative to those who did not, with a similar change in resilience. Qualitative findings regarding impulse control and emotional resilience provided positive findings. Originality/value: iHEART may be a promising new intervention offering a step change in mental health education for improving resilience, mental well-being and the ability for participants to navigate psychological challenges.